miR-276 and miR-182013-5p modulate insect metamorphosis and reproduction via dually regulating juvenile hormone acid methyltransferase - Jiasheng Song; Wanwan Li; Lulu Gao; Qiang Yan; Xinyan Zhang; Mingzhi Liu; Shutang Zhou (Communications Biology)
Abstract Juvenile hormone (JH) represses insect metamorphosis and stimulates reproduction. JH titers are generally low in juveniles, drop to a nadir during metamorphosis, increase after eclosion and peak in vitellogenic phase. We found that Jhamt, a rate-limiting enzyme in JH biosynthesis, mirrors JH titer patterns in the migratory locust. Knocking down Jhamt reduced JH titers, led to precocious nymphal ecdysis, metamorphosis and impaired vitellogenesis. Jhamt is negatively regulated by miR-276 and positively by miR-182013-5p. miR-276 is abundant in late nymphal but low in adults, while miR-182013-5p shows the opposite pattern. In nymphs, miR-276 binds more to Jhamt, while in adults, miR-182013-5p dominates. Functionally, miR-276 reduced Jhamt and JH levels, shortening nymphal development and inhibiting Vg expression. Conversely, miR-182013-5p increased Jhamt and JH levels, prolonging nymphal development and enhancing Vg expression. Our findings identify miR-276 and miR-182013-5p as dual regulators in JH biosynthesis, acting as “brake” and “accelerator,” respectively. This study provides new insights into JH titer fluctuations and miRNA regulation in insect metamorphosis and reproduction.